1964
DOI: 10.1063/1.1713436
|View full text |Cite
|
Sign up to set email alerts
|

Web Growth of Semiconductors

Abstract: A novel process for growth of diamond-lattice semiconductors is described, and a model is proposed for the growth mechanism. For germanium the process yields extended thin flat sheets, typically 1 cm wide and 0.1 mm thick, of good crystalline quality and relatively flat {111} surfaces. The sheet, or web, freezes from a liquid film drawn up by surface tension between two coplanar dendrites which originate from a single seed and are grown from the melt simultaneously with the sheet. Resistivity throughout the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Regarding the former, it is well known that the ͗112͘ dendrite is bounded by ͕111͖ planes and that it contains parallel twins. [8][9][10][11][12][13][14][15][16][17][18][19][20] To investigate the structural features of the ͗110͘ dendrite, we analyzed its crystallographic orientation ͑Fig. 4͒.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the former, it is well known that the ͗112͘ dendrite is bounded by ͕111͖ planes and that it contains parallel twins. [8][9][10][11][12][13][14][15][16][17][18][19][20] To investigate the structural features of the ͗110͘ dendrite, we analyzed its crystallographic orientation ͑Fig. 4͒.…”
Section: Methodsmentioning
confidence: 99%
“…It was also shown that the preferential growth directions of Si faceted dendrites are ͗112͘ and ͗110͘. 18 Such features of faceted dendrites can be applied in technologies for growing thin Si ribbon crystals 13,14 and polycrystalline Si ingots 21,22 for solar cells. A growth mechanism for the dendrite preferentially grown along the ͗112͘ direction, hereafter referred to as a ͗112͘ dendrite, was first proposed in 1960.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, twin-related dendrites of Si or Ge, which are the so-called ''faceted dendrites,'' have attracted much attention from both scientific and technological viewpoints due to their unique crystal structures. The surface of the dendrite is bounded by f111g habit planes, and at least two parallel twins exist at the center of the dendrite [1][2][3][4][5][6][7][8][9][10][11][12]. It is also known that the growth rate of a faceted dendrite is larger than equiaxed grains [12,13].…”
mentioning
confidence: 99%
“…It is also known that the growth rate of a faceted dendrite is larger than equiaxed grains [12,13]. Such features can be applied in technologies for growing thin Si ribbon crystals [6,7] and polycrystalline Si ingots [13] for solar cells. The growth model of faceted dendrites was proposed in 1960 [3,4].…”
mentioning
confidence: 99%
“…The features of a faceted dendrite are different from dendrites of metallic alloys in terms of the following[19][20][21][22][23][24][25][26][27]:…”
mentioning
confidence: 99%